Analysis of Safety Issues of Using Statins in Patients with Diabetes and Hypothyroidism - V. V. Arkhipov; G. I. Gorodetskaya; O. A. Demidova; T. V. Alexandrova; A. A. Alexandrov (Безопасность и риск фармакотерапии)
The widespread use of statins in clinical practice necessitates a systematic approach to the risk and safety assessment. The aim of the study was to analyze information about adverse reactions to statins and their specific causes in patients with hypercholesterolemia accompanied by diabetes and hypothyroidism. The paper compares statin products (simvastatin, atorvastatin, pravastatin, rosuvastatin, and fluvastatin) in terms of the frequency of the most significant adverse reactions—statin-induced myopathy, liver damage, secondary hyperglycemia. It discusses specific causes of adverse reactions to statins in patients with hypothyroidism and diabetes. It was demonstrated that the use of statins in patients with compensated hypothyroidism, who have CC and TC allelic variants of the SLCO1B1*5 gene (c.521T>C), is associated with a higher risk of developing statin-induced myopathies. The adjustment of statin doses, especially in patients with hypothyroidism and diabetes, should be made based on the results of pharmacogenetic testing for SLCO1B1*5 (c.521T>C) allelic variants. The results of dynamic clinical and laboratory control of the hepatic transaminase level, as well as the levels of glucose, glycated hemoglobin, and thyroid-stimulating hormone should be the key factors to be taken into account when adjusting treatment plans in this group of patients. The paper analyses polymorphisms of genes which are associated with resistance to statin therapy in patients with diabetes. Thus, the use of statins for primary prevention and treatment of cardiovascular diseases in patients with hypercholesterolemia accompanied by diabetes and/or hypothyroidism, requires a comprehensive assessment of the risk/benefit ratio.